High School Teachers' perception about sexual education at school (Revista Internacional de Formação de Professores, 2017)
The goal of this research is investigate the perception of the High School teachers about Sexual Education at schools. For this, was conducted a research involving fifty different teachers that teaching at public high school - at São Paulo. It was applied a questionnaire to teachers and analyzed of all data according to the content analysis. The data showed that most of the teachers do not have a specific training proper, for working with sexual education students with its, and a large part of percentage of these not develop a working with thematic often. Those teachers that develop such projects are by several factors, for example on its own initiative, for the thematic inserted being within the curricular school project, among other reasons. The emphasis given by that teachers when implement sexual education projects is more in Biological and Psychological aspects instead of social aspects. Other research will be carried out so that we can have clarity increasingly about how sex education is present in formal education context and as what the possibilities and challenges surrounding this topic.
Keywords: Sexual Education. High School. Teachers’ Perception.